Systematic Literature Review: Penerapan Model Project Based Learning untuk Meningkatkan Keterampilan Berpikir Kreatif Siswa - Klemens Mere (Journal on Education, 2023)
Creative thinking skills are the ability of students to come up with or develop new ideas without being limited by pre-existing ideas flexibly. The purpose of this research is to analyze the application of Project Based Learning model in improving students' creative thinking skills. The method used in qualitative research with library studies or System Literature Review (SLR). The goal is to analyze the comparison of existing theories with previous theories in the research literature. The literature used is literature from research results or studies presented in scientific articles. The literature used is literature from research results or studies presented in scientific articles. All articles used are sourced from the electronic data literacy search engine Mendeley and Google Scholar. Based on the results and discussion through systematic literature review in this article, there is a conclusion that the application of Project Based Learning model can improve students' thinking skills.